2015
DOI: 10.1097/pas.0000000000000333
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Budding Is an Independent Adverse Prognostic Factor in Pancreatic Ductal Adenocarcinoma

Abstract: Tumor budding is a well-established adverse prognostic factor in colorectal cancer. However, the significance and diagnostic reproducibility of budding in pancreatic carcinoma requires further study. We aimed to assess the prognostic significance of tumor budding in pancreatic ductal adenocarcinoma, determine its relationship with other clinicopathologic features, and assess interobserver variability in its diagnosis. Tumor budding was assessed in 192 archival cases of pancreatic ductal adenocarcinoma using he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
87
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(94 citation statements)
references
References 24 publications
7
87
0
Order By: Relevance
“…Multiple series have shown that increased tumor budding is associated with lymph node metastasis, distant metastasis, and recurrence in colorectal adenocarcinomas [15,16]. Similar studies have also shown a similar relationship in adenocarcinomas of the ampulla [21], esophagus [22,23], and pancreas [24]. However, very little research has been performed evaluating tumor budding in GAC [18,25,26].…”
Section: Accepted Manuscriptmentioning
confidence: 87%
See 2 more Smart Citations
“…Multiple series have shown that increased tumor budding is associated with lymph node metastasis, distant metastasis, and recurrence in colorectal adenocarcinomas [15,16]. Similar studies have also shown a similar relationship in adenocarcinomas of the ampulla [21], esophagus [22,23], and pancreas [24]. However, very little research has been performed evaluating tumor budding in GAC [18,25,26].…”
Section: Accepted Manuscriptmentioning
confidence: 87%
“…Because all cases were reviewed concurrently in our study, no assessment of interobserver agreement was practical. Only a subset of the published studies quantifies interobserver variability with kappa values ranging from moderate to very good [15,16,23,24,32,33]. P=0.07).…”
Section: Accepted Manuscriptmentioning
confidence: 97%
See 1 more Smart Citation
“…Morphologically, tumor budding is defined as the presence of single tumor cells or isolated small clusters of tumor cells (up to 5 tumor cells) scattered in the stroma at the invasive front; it represents a type of local diffusely infiltrative growth and occurs when tumor cells detach from the invasive tumor margin and migrate into the surrounding stroma. Tumor budding has frequently been observed in several types of solid tumors, including colorectal cancer [12], esophageal carcinoma [13], pancreatic carcinoma [14, 15], breast cancer [16, 17], lung carcinoma [18, 19], and endometrial carcinoma [20]; tumor budding has been recognized as an aggressive indicator and an adverse prognostic factor [1220]. Moreover, as a result of its significant prognostic value, tumor budding is recommended by the International Union against Cancer for inclusion in the pathological report of colorectal cancer as an additional prognostic factor [21].…”
Section: Introductionmentioning
confidence: 99%
“…Especially in aggressive PDAC, the invasive tumour margin includes the presence of de‐differentiated carcinoma cells detached from the main tumour and showing signs of epithelial–mesenchymal transition (EMT), identified histologically as ‘tumour budding’ (BD) . Recent studies have confirmed that an increasing number of tumour buds has a significant adverse impact on patient survival and have identified BD as an independent prognostic factor in PDAC . All these studies provided evidence for an improved prognostic stratification of PDAC patients based on the assessment of BD.…”
Section: Introductionmentioning
confidence: 99%